(untitled) (Journal of Medical Sciences, 2024)
Medical waste management is one of the biggest challenges facing our world today, as environmentalists are increasingly concerned about the negative health effects resulting from irresponsible handling of it. although the global spread of wet cupping treatment centers, limited research available about the management of the waste generated by them. World Health Organization classified them as hazardous and infectious wastes, therefor, this study worked to collect data on how wet cupping centers in the city of Misrata deal with their medical waste, and evaluate the volume of waste generated And the problems facing medical waste management in these centers. The study sample consisted of 20 cupping centers, and it included 49 participants. Questionnaires and personal interviews were used to collect data, and then analyzed using SPSS. According to the current study, the average production of cupping waste is about 12.376 kg per day in each center, with weakness of the systems used in dealing with this waste in terms of separation, collection, storage and final disposal. The study found that sharps caused 51.02% of study sample, and 34.69% of them were injured with broken therapeutic cups as a result of not separating sharp tools from others. Blood waste found to be disposed with general wastes due to lack of medical disposing facilities and local control authorities. This necessitates raising the level of responsibility at these centers and following the necessary laws to protect workers and the environment. This study recommended to apply the global and local laws. To improve the level of dealing with medical waste resulting from cupping centers